Representasi Trauma dan Makna Rumah dalam Film Rumah untuk Alie (2025): Analisis Semiotika Roland Barthes - Saputra, Adi; Warmansyah, Imam; Munandar (TAMADDUN, 2025)
The film Rumah untuk Alie (2025) is an Indonesian family drama that highlights issues of domestic violence, bullying, and the psychological trauma experienced by a teenage girl who is blamed for her mother’s death. This study aims to analyze the representation of trauma and the meaning of “home” in the film through Roland Barthes’ semiotic framework, which consists of three levels of meaning: denotation, connotation, and myth. The research method employs a qualitative-descriptive analysis with data collected from observations of the official trailer, published synopses, promotional materials, media, and media reviews. The findings show that the home functions not merely as a physical space but as a symbolic site of deep trauma for the character Alie. At the denotative level, the home appears as the primary setting for verbal and physical violence perpetrated by her father and brothers. At the connotative level, the home generates metaphorical meanings related to emotional wounds, gendered injustice, and psychological pressure within a patriarchal family structure. At the mythic level, the film deconstructs and critiques cultural assumptions about the home as the safest place and the idealization of the harmonious family. The study concludes that Rumah untuk Alie illustrates how domestic violence becomes embedded through everyday symbols and underscores the necessity of emotional support.